2021
DOI: 10.1007/s10565-021-09616-x
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene microplastics induce an immunometabolic active state in macrophages

Abstract: Anti-and pro-in ammatory responses in macrophages are in uenced by cellular metabolism.Macrophages are the primary phagocyte in mucosal environments (i.e., intestinal tract and lungs) acting as rst-line defense against microorganisms and environmental pollutants. Given we now face extensive microplastic contamination of our food and water sources, we aimed to examine the metabolic response in macrophages to microplastic particles (MP). Utilizing murine macrophages, we assessed the metabolic response of macroph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 70 publications
(89 reference statements)
1
18
0
Order By: Relevance
“…MNP-exposed macrophages revealed a decrease in mitochondrial membrane potential, which suggests that phagocytosis of MNPs by murine macrophages can induce an immunometabolic active state [ 70 ]. These findings suggest a significant impact of alterations in macrophage metabolism caused by MNP exposure on immunity and inflammation.…”
Section: Toxicities Of Micro- and Nanoplastics On Mitochondriamentioning
confidence: 99%
“…MNP-exposed macrophages revealed a decrease in mitochondrial membrane potential, which suggests that phagocytosis of MNPs by murine macrophages can induce an immunometabolic active state [ 70 ]. These findings suggest a significant impact of alterations in macrophage metabolism caused by MNP exposure on immunity and inflammation.…”
Section: Toxicities Of Micro- and Nanoplastics On Mitochondriamentioning
confidence: 99%
“…Plastics can cause adverse health effects through both physical- and chemical-mediated pathways. Notably, the large surface areas of nano- and microplastics can interrupt local biomolecular complexes and invoke downstream effects including inflammation, oxidative stress, , and apoptosis . Chemical-mediated toxicity is a more significant concern for larger plastics that cannot directly enter the human body ( e.g., food contact materials) through potential leaching or desorption of additives.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that macrophages do not degrade MPs, and this also leads to increased intracellular glycolysis and reduced mitochondrial respiration. 73 In conclusion, exposure to MPs can cause inflammatory responses in animals such as fish, mice, and humans, and MPs can provide a good growth environment for microorganisms to enhance their damage to the body. In addition, the inflammatory response caused by MPs is inextricably linked to its diameter, shape, and surface roughness.…”
Section: Mps and Geno-toxicology Effectsmentioning
confidence: 97%